2016
DOI: 10.4155/fsoa-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Improving Public Awareness and Outcomes for Oral Cancer

Abstract: Catherine Poh speaks to G Westcott, Commissioning Editor: Dr. C Poh gained a dental degree from the National Taiwan University in Taipei, Taiwan and went on to gain her PhD from the University of British Columbia in 1997, looking into molecular biology in oral cancer. In addition to her current role an associate professor in the Faculty of Dentistry at the University of British Columbia, she is a senior clinician scientist at the Integrative Oncology Department of the BC Cancer Agency's Research Centre. She ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…It is proven that masses must be educated on the urgency for an early consultation for patients with suspected oral lesions [21, 22]. This study has demonstrated a low level of knowledge around the symptoms of oral cancer, and also a tendency to attribute disease occurrence to divine will.…”
Section: Discussionmentioning
confidence: 95%
“…It is proven that masses must be educated on the urgency for an early consultation for patients with suspected oral lesions [21, 22]. This study has demonstrated a low level of knowledge around the symptoms of oral cancer, and also a tendency to attribute disease occurrence to divine will.…”
Section: Discussionmentioning
confidence: 95%
“…This can be important for early detection as it has been stated that premalignant and early oral cancer lesions are often asymptomatic, with no pain or discomfort felt by patients. 33…”
Section: Promotion Of Oral Cancer Awarenessmentioning
confidence: 99%
“…The two techniques that have gained the most ground are autofluorescence and contrast enhanced near‐infrared fluorescence (NIR) . Fluorescence imaging requires systemic administration of a cancer targeting agent coupled with a fluorophore and imaging time‐point with the best tumor‐to‐background ratio (TBR).…”
Section: Introductionmentioning
confidence: 99%